Comparisons of the stages and psychosocial factors of smoking cessation and coping strategies for smoking cessation in college student smokers: Conventional cigarette smokers compared to dual smokers of conventional and e‐cigarettes. Issue 4 (4th November 2018) - Oh, HyunSoo; Im, BoAe; Seo, WhaSook
Abstract: Aim: This study was conducted to compare conventional cigarette and dual smokers (users of both conventional and e‐cigarettes) with respect to the stages of smoking cessation behavior change and psychosocial factors and coping strategies for smoking cessation among college students. Methods: Using convenience and snowball sampling methods, 300 college student smokers were recruited. The data were collected from July to December, 2016. The data included the general characteristics of the participants, information related to smoking and smoking cessation, the stages of smoking cessation behaviors, self‐efficacy in, and barriers to, smoking cessation, and adoption of coping strategies for smoking cessation. Results: The prevalence of e‐cigarette use in the cohort was 19.3%. Nicotine dependence in the dual smoker group was significantly higher than that in the conventional cigarette smoker group. No significant intergroup differences were observed for the stage of smoking cessation behavior and self‐efficacy in, and perceived barriers to, smoking cessation. However, the dual smokers had a significantly higher prevalence of quit attempts and were more likely to adopt smoking cessation coping strategies. Conclusions: The findings indicated that the dual smokers had higher levels of nicotine dependence, but were more likely to attempt to quit smoking and adopt smoking cessation coping strategies. This implies that dual smokers might find it more difficult to quit smoking related to higher nicotine dependence, despite having a higher motivation for smoking cessation. These characteristics should be considered when developing smoking cessation strategies for e‐cigarette smokers. In addition, different approaches to smoking cessation education should be used for e‐cigarette and conventional cigarette smokers.